Penerapan Supervisi Klinis Oleh Kepala Sekolah Dalam Meningkatkan Kinerja Guru Terhadap Proses Belajar Mengajar Di SMK Swasta Madani - Yeni Saufina Siregar; Dian Ratna Puri; Yenni Khairani Pane; Yasaratodo Wau (Program Studi Pendidikan Biologi, 2023)
Teachers need clinical supervision to improve their professional performance. Principals can conduct performance coaching for teachers to help them manage the teaching and learning process through clinical supervision. The principal of SMK Swasta Madani can carry out clinical supervision through various activities including meetings, observations, evaluations, and analysis. This research approach uses qualitative descriptive research. Data collection methods come from literature studies, interviews, and observations. 1) The Head of SMK Swasta Madani carries out clinical supervision in stages as a coaching effort for teachers to improve teacher professionalism in teaching; 2) Principals who conduct clinical supervision are able to improve teacher performance better; and 3) Principals who carry out clinical supervision must understand and have strategies capable of providing change for teachers. Such are the findings of this study.